Iodine-complex directed synthesis of PbS quantum dots with enhanced electronic coupling for NIR photodetection - He, Shenghui; Qian, Guojiang; Zhang, Cong; Yin, Xingtian; Que, Wenxiu (Frontiers in Chemistry, 2025)
Lead sulfide (PbS) colloidal quantum dots (CQDs) are promising materials for near-infrared (NIR) photodetection. However, conventional synthetic approaches often rely on long-chain organic ligands that impede charge transfer, necessitating complex post-synthetic ligand exchanges. Here, we introduce an Iodine-Complex Directed Synthesis (ICDS) method that enables the direct synthesis of iodide-passivated PbS-I QDs in polar solvents, thereby bypassing traditional hot-injection routes and ligand exchange processes. The PbS-I QDs demonstrated a reduction in interparticle spacing and enhanced electronic coupling, attributable to the elimination of long-chain insulating ligands. Consequently, these PbS-I QDs exhibited a photoluminescence emission peak at 1,060 nm, characterized by a distinct spectral profile indicative of efficient radiative recombination. To assess their practical applicability, the PbS-I QDs were applied in two distinct NIR photodetector architectures: sensitized photo field-effect transistors (photo-FETs) and photodiodes. The photo-FETs have demonstrated a specific detectivity of 1.63 × 1011 Jones with rise and decay times recorded at 46.2 ms and 46.3 ms, respectively. In contrast, the photodiodes displayed superior response times, characterized by rise and decay times of 10 μs and 15 μs, respectively. These results demonstrate the effectiveness of the ICDS method in producing high-quality QDs and its potential for enabling high-speed, low-noise NIR photodetectors.